Comparative Analysis of Environmental Protection Provisions in Construction Procurement: A Case Study of Nepal’s Projects Funded by National and International Agencies - Acharya, Sagar; Kumar Bhattarai, Subash; Khanal, Pratik; Khanal, Preju; Dahal, Diksha (International Journal on Engineering Technology, 2024)
This study investigates the environmental protection provisions embedded in procurement processes of construction projects in Nepal, funded by various national and international agencies. The research aims to compare and analyze the environmental safeguarding measures outlined in bidding documents from different funding sources, along with examining relevant legal frameworks and policies governing environmental protection in construction projects. Through a qualitative approach and content analysis methodology, the study delves into the scope, limitations, and significance of environmental considerations in construction procurement. Findings reveal diverse approaches across funding agencies, highlighting the emphasis on contractor responsibilities, safety measures, and project management. While Nepal’s standard bidding documents establish foundational environmental provisions, projects funded by international agencies demonstrate a higher commitment to environmental sustainability. The study underscores the importance of comprehensive environmental measures in construction projects to mitigate ecological impact and promote long-term environmental conservation.